ANALYSIS OF WORKING POSTURE IN METAL DUCT WELDING USING THE REBA (RAPID ENTIRE BODY ASSESSMENT) METHOD AT PT XYZ - Delicia Salsabila Alfani; Mochamad Tutuk Safirin (Center for Study and Journal Management FTI UMI, 2023)
PT XYZ is a make-to-order private company engaged in fabrication, design, and construction. PT XYZ has received repetitive orders, especially for Metal Duct products. There are still many worker complaints in the production process, especially in the welding section that does not apply ergonomic work postures. This study aimed to determine the work posture score so that the action level category of workers in the metal duct welding section at PT. XYZ with the REBA (Rapid Entire Body Assessment) method and suggestions for correct working posture improvements in the welding section at PT. XYZ. The results showed that the highest REBA score was for welding worker 5, who got a REBA score of 11, where this value got an action level 4 value which is a very high risk, and there is a need for corrective action right now. Welding workers 3 get a REBA score of 9. This value gets an action level 3 score, which is a high risk, and immediate corrective action is needed. Welding workers 1, 2, and 4 get the same REBA score of 5. This value gets an action level 2 score, which is moderate risk and needs improvement. From the final value obtained, it can be proposed to improve work posture for welding workers who get a work posture risk value of 2, where this value is lower than the initial work posture risk value.